Implementasi Sistem Kenaikan Pangkat Otomatis (KPO) Berbasais Online Pada Kantor Regional VI Badan Kepegawaian Negara Di Kota Medan - Dessy Savitri; Siti Hazzah Nur (SAJJANA: Public Administration Review, 2023)
The implementation of a system of automatic promotion based online is one of the policies formulated by the state human resources agency, explained one about the automatic promotion. Because before added this system, process of proposal promotion done manually by physical attach the file to be brought to the state personnel board of the city of Medan. The purpose of this study to described the made in automatic promotion system based on online and implemented in regional offices VI employment agency state in the city of Medan. This study using theory Van Meter and Van Horn. Descriptive methods used is the method with a qualitative approach using theory Van Meter andVan Horn policy covering standards and objectives, resources, the relationship between organization (communication), characteristic of implementing agent, the social conditions, economic and political implementor and disposition. In this research data collection techniques used technique interview, observation and documentation. The result of the research indicated that the implementation of a system of automatic promotion based online at regional offices VI national civil service agency in the city of Medan was doing well, conforming to the standards and objectives set policy